Her hometown soldier's return - Bristow, LeAnne (Harlequin heartwarming, 2024)
She can help heal his injuries...But what about his heart? Millie Gibson has been waiting for her brother's best friend to finish his military service, but when Randon Farr has at last been discharged from the army, he returns with injuries that go beyond his wounded shoulder. As a nurse, Millie isn't afraid of the scars he now carries. There's nothing she won't do for her stubborn, brave soldier. But with Randon determined to sell the family cabin and leave Arizona for good, Millie will have to choose between the man she's been waiting for and the life she's built here in Coronado.